ADSORPTION PROPERTIES OF SENSOR MATERIALS BASED ON SNO2 PROMOTED WITH 3-D METALS: UDC 541.128, 543.272.2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Adsorption and catalytic properties of sensor materials based on SnO2 promoted by 3-d metals (Co, Fe, Ni, Cu) are investigated. Maximal products desorption temperatures for all catalysts on a few tens of degrees are lower than total-lot conversion temperatures of reagents for H2 and CO oxidation reaction. It is to be evidence that under catalysis desorption step is not limited.
Keywords: -